Penerapan Pembelajaran Diferensiasi PAI dan BP untuk Membantu Siswa Kelas XI F6 Memahami Materi - Anugrah, Muhammad Ichsan; Muliati, Indah (YASIN, 2025)
This study is motivated by the fact that the education system has not fully provided flexible learning tailored to the needs and abilities of individual students, despite the diverse backgrounds in readiness, interests, talents, and learning styles within each classroom. One approach that can accommodate this diversity is the differentiated instruction model. The aim of this study is to explore the implementation of differentiated instruction and to identify the challenges and solutions faced by teachers in its application. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. The findings show that differentiated instruction is implemented through identifying student needs; delivering materials at varying levels of difficulty; adjusting teaching methods to students' learning styles; setting flexible assessment criteria; and allowing students to give feedback on their learning experiences. Challenges faced by teachers include a heavy administrative workload and limited classroom space, particularly for students with a kinesthetic learning preference. Solutions include efficient time management; thorough lesson preparation; and the use of the surrounding environment as part of the teaching strategy. The conclusion of this study is that differentiated instruction enhances the quality and effectiveness of learning on an individual basis. The implications of this study highlight the importance of teacher training and systemic support to ensure optimal implementation of differentiated learning in Islamic Religious Education as well as other subjects.